2019
DOI: 10.3390/c5010004
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Mechanisms of Salt Precipitation during CO2 Injection in Sandstone

Abstract: Deep saline reservoirs have the highest volumetric CO2 storage potential, but drying and salt precipitation during CO2 injection could severely impair CO2 injectivity. The physical mechanisms and impact of salt precipitation, especially in the injection area, is still not fully understood. Core-flood experiments were conducted to investigate the mechanisms of external and internal salt precipitation in sandstone rocks. CO2 Low Salinity Alternating Gas (CO2-LSWAG) injection as a potential mitigation technique t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Numerical simulations predict significant salt-induced pressure build-up around the CO 2 injection well, the preferential salt precipitation area 15 – 17 , even for high permeability rocks and low injection rates 18 , 19 . Experimental studies have confirmed CO 2 —induced salt precipitation in porous media from lab-on-chip experiments 6 , 20 and core scale flow-through tests 21 23 . Experimental observations show that the precipitation process starts after a transition period post—CO 2 injection, forming early pore scale crystals in the brine, followed by late polycrystalline aggregates at the CO 2 —brine interface 7 .…”
Section: Introductionmentioning
confidence: 74%
“…Numerical simulations predict significant salt-induced pressure build-up around the CO 2 injection well, the preferential salt precipitation area 15 – 17 , even for high permeability rocks and low injection rates 18 , 19 . Experimental studies have confirmed CO 2 —induced salt precipitation in porous media from lab-on-chip experiments 6 , 20 and core scale flow-through tests 21 23 . Experimental observations show that the precipitation process starts after a transition period post—CO 2 injection, forming early pore scale crystals in the brine, followed by late polycrystalline aggregates at the CO 2 —brine interface 7 .…”
Section: Introductionmentioning
confidence: 74%
“…This localized precipitation subsequently narrowed these pore spaces, restricting fluid flow. This phenomenon, observed in studies utilizing similar core flooding techniques, can significantly restrict fluid flow and contribute to the observed permeability reduction …”
Section: Resultsmentioning
confidence: 98%
“…This phenomenon is particularly pronounced in and around the borehole, where substantial volumes of dry CO 2 traverse the rock formation. This effect is generally more common in CO 2 storage in saline aquifers, but this may also happen in CO 2 -EOR . In this work, an attempt has been made to capture the effect of halite precipitation and associated changes in porosity and permeability.…”
Section: Methodsmentioning
confidence: 99%
“…This effect is generally more common in CO 2 storage in saline aquifers, but this may also happen in CO 2 -EOR. 62 In this work, an attempt has been made to capture the effect of halite precipitation and associated changes in porosity and permeability.…”
Section: Modeling Of Mineral Dissolution and Precipitation Controlled...mentioning
confidence: 99%